A Clinico-pathological Study of Transvaginal Endometrial Thickness Measurement in Asymptomatic Postmenopausal Patients and Patients with Postmenopausal Bleeding - Ayse Filiz Gokmen Karasu; Seda Ates; Tugba Gurbuz; Nurhan Sahin; Taha Takmaz; Serdar Aydin (Medical Network, 2019)
Objective: We aimed to determine the frequency of endometrial pathologies of patients who presented to our outpatient clinic with postmenopausal bleeding (PMB) and asymptomatic menopausal patients with a finding of thickened endometrium on transvaginal ultrasonography. Study Design: This study was performed at Bezmialem University Hospital. Women who presented to our clinic from January 2015 to January 2017 were analyzed. Patients were divided to two groups. All patients underwent transvaginal ultrasound with a 7.5 MHz probe. Endometrial sampling was performed by either blind D&C (dilatation & curettage) or pipelle sampling. We excluded patient specimens that were obtained by hysteroscopy. Results: Electronic records of a total of 368 patients in menopause were inspected. Out of these patients; 287 (78%) underwent endometrium sampling indicated by bleeding. Eighty-one patients (22%) were asymptomatic; however, a thickened endometrium echo on TVUSG examination (≥ 5 mm) was suspected. The median age was 57 (42-85). In both groups the two leading causes of endometrial pathology was; endometrial polyps followed by proliferative endometrium. The frequency of endometrial cancer was 9.4 % for the PMB group and 1.2 % in the asymptomatic patient group Conclusion: Evaluation of PMB as soon as possible is essential for diagnosing endometrial pathologies. Role of endometrial thickness is decisive in detecting patients at high risk for malignancy especially with comorbid conditions. Histopathological evaluation is mandatory for ruling out malignancy.